Oestrogen receptor alpha gene polymorphisms relationship with semen variables in infertile men. (3rd July 2013) - Zalata, A.; Abdalla, H. A.; El‐Bayoumy, Y.; Mostafa, T.
Summary This study aimed to assess the association of oestrogen receptor alpha (ER‐α) gene polymorphisms and semen variables in infertile oligoasthenoteratozoospermic (OAT) men. In all, 141 men were grouped into fertile men (n = 60) and infertile OAT men (n = 81). They were subjected to assessment of semen analysis, acrosin activity, serum reproductive hormones and genotyping of ER‐α gene. Frequencies of p and x alleles in ER‐α gene PvuII and XbaI polymorphisms were more prevalent among fertile men compared with infertile OAT men. Presence of P and X alleles was associated with increased incidence of male infertility for genotypes PP, XX compared with genotypes pp and xx (OR = 2.8; 95% CI: 2.36–6.97; P = 0.001 and OR = 4.1, 95% CI: 1.49–11.39; P = 0.001, respectively). The mean of semen variables and sperm acrosin activity were significantly higher in cases associated with pp than PP and in xx than XX genotypes of ER‐α gene. Mean levels of all serum reproductive hormones demonstrated nonsignificant differences in different ER‐α genotypes except oestrogen that was elevated in PP and XX ER‐α gene genotypes. It is concluded that as oestrogen is concerned in male gamete maturation, ER‐α gene polymorphisms might play a role in the pathophysiology of male infertility.